The Influence of Learning Models Picture and Picture Help Media Puzzle toward the PKN Learning Results of Class IV Students at UPTD SD Inpres Labat - Taneo, Marni Eunike; Nahak, Roswita Lioba; Nitte, Yulsy Marselina (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The picture and picture learning model is a learning medium that uses pictures and is paired or sequenced into a logical sequence. The aim of this research is to determine the effect of the picture and picture learning model in Civics learning on the learning outcomes of class IV students at UPTD SD InpresLabat. This type of research is quantitative. The experimental design used in this research was a non-equivalent control group design. In this study, the population was class IV students at UPTD SD Inpres Labat, totaling 40 students, consisting of class A totaling 20 and class B totaling 20. And the sample from this research was all class IV students totaling 40 students, where class A was control class and class B as the experimental class. The data collection techniques used in this research are tests and documentation and the instruments used in this research are post test and pre test. The data analysis used in this research is the normality test, homogeneity test and hypothesis test or t-test. Based on the results of the research and discussions conducted regarding: the influence of the picture and picture learning model assisted by puzzles on the Civics learning outcomes of class IV UPTD SD InpresLabat students, it can be concluded that there is a significant influence between the picture and picture learning model and student learning outcomes. This is proven by the results of hypothesis testing using a paired sample test with a significance level of 0.05. The results of the research show a significance value (2-tailed) of 0.00 < 0.05, so it is concluded that Ho is rejected and Ha is accepted. This means that student learning outcomes are different between the experimental class and the control class, or in other words, there is a significant difference between the picture and picture learning model assisted by puzzles and the Civics learning outcomes of class IV students at UPTD SD Inpres Labat.